Does ESG Performance Affect Financial Performance? Evidence from Indonesia - Ihsani, Azhar Nafis; Nidar, Sulaeman Rahman; Kurniawan, Meinanda (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
Economic, social, and environmental issues are currently becoming major worldwide issues. Geopolitical, social, and economic power streams have focused on ESG goals, encouraging companies, investors, and governments to apply them to every aspect of business. The current constraint is that Indonesian business stakeholders are still typically focused on short-term profits, which are intended to transform towards long-term sustainability. This study examines the effect of ESG performance on corporate financial performance. The primary analysis tool in this study uses panel data regression analysis with the Random Effect Regression Model. The sample was selected from 23 companies listed on the Indonesia Stock Exchange, with an observation period of 2018–2020. The results of this study indicate that the performance of ESG and its sub-dimensions has a positive effect on the financial performance of accounting-based companies as measured using ROA. However, on a market-based proxy with Tobin's Q, ESG performance and its sub-dimensions have not been able to influence the corporate financial performance. Some important reasons companies are involved in environmental, social, and governance activities are to create competitive advantage, reduce company risk, improve market performance, and enhance the company's sustainable development capabilities.